Extending the functionality of arrowroot starch by thermally assisted high hydrostatic pressure - Ludmilla de Carvalho Oliveira; Bill MacNaughtan; Ourania Gouseti; Flávia Villas‐Boas; María Teresa Pedrosa Silva Clerici; Serafim Bakalis; Syahrizal Muttakin; Nello Cristianini (2021)
The modification of native arrowroot starch (NAS) properties by thermally assisted high hydrostatic pressure (HHP) was investigated. Changes in the structure of the granules were produced by HHP. This was enhanced when HHP was applied together with a temperature increase to 50℃, for 15 or 25 min. Processing at 400 MPa/25℃ had minimal effect. As pressure and/or temperature increased, processed arrowroot starches progressively lost the Maltese cross and granular structure. There was also a decrease in the enthalpy of the gelatinization which occurred between 61.3 and 80.3℃. The relative crystallinity of NAS was reduced, depending on the severity of treatment, by 6.81%–35.74%. A principal components analysis showed a clear trajectory depending on processing conditions. The most severe treatment 650 MPa/50℃ did not produce complete gelatinization. Thermally assisted HHP demonstrated advantages over at 25℃ and produced a physically modified version of the arrowroot starch, with potential as a clean label ingredient. Novelty impact statement: This study with arrowroot starch (AS) has revealed a pronounced effect of high hydrostatic pressure (HHP) when applied together with mild temperature (50℃), compared with conventional processes at room temperature, and consequent lowering of onset pressure for structural changes of starch. Modified AS with a several different functionalities may be produced by thermally assisted HHP, whose techno-functional properties correspond well with the measurements of structural order. The results of this work support the industrial potential of this unconventional starch as a clean label ingredient.